2006
DOI: 10.1177/0022427805280069
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development and Physical Victimization in Adolescence

Abstract: Although much research has established a link between pubertal development and adolescent involvement in offending, drug use, and other adverse outcomes, no research has examined whether puberty is associated with experiences of violent physical victimization. This is an unfortunate oversight because researchers are only beginning to understand the range of adverse outcomes associated with puberty-and information on this front bears relevance for public health discussions regarding the consequences of pubertal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 64 publications
6
134
0
Order By: Relevance
“…In order to combine these two items into a single gender-neutral variable, the male puberty variable was dichotomized so that a score of zero indicated that the pubertal changes had not yet begun or had barely started, and a score of one indicated that the changes were definitely underway or seemed complete. Although we cannot be certain that these measures represent exactly the same level of pubertal development for both genders, the proportion of boys relative to girls who have reached puberty according to the measure (i.e., more females than males) is consistent with previous research (Haynie and Piquero, 2006;Underwood and Van Wyk, 1992).…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In order to combine these two items into a single gender-neutral variable, the male puberty variable was dichotomized so that a score of zero indicated that the pubertal changes had not yet begun or had barely started, and a score of one indicated that the changes were definitely underway or seemed complete. Although we cannot be certain that these measures represent exactly the same level of pubertal development for both genders, the proportion of boys relative to girls who have reached puberty according to the measure (i.e., more females than males) is consistent with previous research (Haynie and Piquero, 2006;Underwood and Van Wyk, 1992).…”
Section: Methodssupporting
confidence: 87%
“…Additionally, approximately 64% (61% of males and 67% of females) of the target youth (G3) had reached puberty by age 12-13 in 1997. This is consistent with research that finds that males tend to reach puberty at older ages than females (Haynie and Piquero, 2006;Underwood and Van Wyk, 1992). On average, G1s had completed less than a high school education (X ‾ = 2.51), had given birth to G2 at the age of 26.06, and 72% had provided an intact family for G2.…”
Section: Sample Characteristicssupporting
confidence: 90%
“…Buka and colleagues (2001) have recently redefined this construct by categorizing different levels of exposure that include primary, i.e., personal victimization, secondary, i.e., violence seen or heard, and tertiary exposures, i.e., learning of violence experienced by others such as friends of family members. While much is already known about predictors and consequences of primary exposures (Christiansen & Evans, 2005;Esbensen & Huizinga, 1991;Haynie & Piquero, 2006;Lauritsen et al, 1992;Loeber, Kalb, & Huizinga, 2001;Menard, 2002;Schreck, 1999;Snyder & Sickmund, 1999), the same cannot be said for secondary exposures that children and adolescents experience in their neighborhoods.…”
Section: Defining Types Of Exposure To Violencementioning
confidence: 99%
“…We now have considerable knowledge about the individual factors contributing to violent victimization (Christiansen & Evans, 2005;Esbensen & Huizinga, 1991;Haynie & Piquero, 2006;Lauritsen et al, 1992;Menard, 2002;Schreck, Fisher & Miller, 2004Snyder & Sickmund, 1999, but our understanding of the broader impacts of violence-and how communities contribute to them-is far more limited (see Lauritsen, 2001;Lauritsen et al, 1992;Selner-O'Hagan, Kindlon, Buyka, Raudenbush, & Earls, 1998;Stewart, Schreck, & Simons, 2006), notwithstanding the calls from some researchers to give greater attention to studying secondary violence (Buka et al, 2001). Scholars have made calls to target the environments in which children live to alleviate violence exposure and the resulting negative consequences (Luther & Goldstein, 2004;Sullivan, Kung, & Farrell, 2004), but such calls do not appear to be empirically grounded in research that indicates structural and social aspects of neighborhoods are any more important than individual risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…But it is notable that in our data, the transition was demonstrably more problematic for sixth graders than for seventh graders. There is evidence that ages 11-13 are a particularly sensitive period for the development of deviant peer influences (see Eccles et al, 1993;Haynie and Piquero 2006;Lacourse et al, 2006;Rudolph et al, 2001) -a time when some but not all children have entered puberty. Also, note that simply delaying adverse consequences by a year produces substantial societal benefits, assuming the transition to middle school has no effect timing of the eventual maturation out of delinquency during early adulthood.…”
Section: Discussionmentioning
confidence: 99%